Histopathological analysis of the gills of fresh water fish Channa gachua exposed to fungicide Pydiflumetofen - Pallavi, Shweta (Recent Research in Science and Technology, 2020)
Indiscriminate use of pesticides has become a serious problem among human and ambient environment. The present study is aimed to assess the damage caused to the fish Channa gachua (family: Channidae) exposed to fungicide Pydiflumetofen. Respiration in Channa gachua mainly occurs through their gills. Any change in the chemical quality of water directly affects the structure and function of gills. Fish gill also helps in osmoregulation and excretion besides respiration. When fish exposed to sub-lethal concentration of Pydiflumetofen pesticide for 10 days, 15days and 20days include Curling and fusion in secondary lamellae, Hyperplasia, reduction in the respiratory surface area of filaments, fusion at the tip of the lamellae, sub lamellar and sub epithelial space occur.